Multi-responsive shape memory and self-healing hydrogels with gold and silver nanoparticles - Kilic H.; CEYLAN D. (My University, 2024)
Nanocomposite smart gels (Nc-x) with self-healing and shape memory properties were designed in different types and size nano particles with temperature or light stimuli. Nc-x networks were prepared by bulk polymerization of stearyl methacrylate (SM) and vinyl pyrrolidone (VP) in the presence of gold and silver nanoparticles. The structure, which does not contain any chemical cross-linkers, is held together by hydrophobic interactions while consisting of dipole-dipole bonds of the VP units and long alkyl groups in the side chains of the SM. Thanks to their crystalline regions, shape memory gels can self-heal with the presence of long hydrophobic chains, and furthermore, the nanoparticles (NPs) incorporated into the structure facilitate the controlled tuning of hydrophilic and hydrophobic properties. Nc-x gels have the ability to self-heal by repairing mechanical damage independently or in the presence of a stimulus, as well as transforming from a temporary form to a permanent form. In vitro experiments on human skin fibroblast cells revealed that cell viability was over 100% after 48 hours and almost complete recovery was observed in scratch experiments at the end of this period. Based on the results obtained, Nc-x gels have been shown to have the potential to be used as a non-invasive wound dressing material alternative to traditional wound closure methods.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Malzeme Bilimi Biyomateryal; Malzeme Bilimi; Mühendislik Bilişim Ve Teknoloji (Eng); Materials Science Biomaterials; Materials Science; Engineering Computing & Technology (Eng); Biyomalzemeler; Malzeme Bilimi (çeşitli); Genel Malzeme Bilimi; Fizik Bilimleri; Biomaterials; Materials Science (miscellaneous); General Materials Science; Physical Sciences